2010
DOI: 10.1007/s12160-010-9181-9
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Function: The Impact of Objective and Subjective Socioeconomic Status on Flow-Mediated Dilation

Abstract: BackgroundAlthough objective and subjective indicators of socioeconomic status (SES) are linked to cardiovascular disease (CVD), little is known about their relationship to endothelial dysfunction, which often precedes CVD.PurposeThis study examined how objective and subjective SES relate to brachial artery flow-mediated dilation (FMD).MethodsFMD was assessed in 72 healthy adults (mean age 36 years). The MacArthur Scale of Subjective Social Status assessed perceived social standing in the USA (SSS-USA) and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 53 publications
2
39
0
1
Order By: Relevance
“…Several prospective and cross-sectional studies in different countries have reported the inverse association of social class with cardiovascular morbidity and mortality independent of conventional risk factors or access to health care, and this association was also found in countries with universal healthcare systems, as in our country [8][9][10][11].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Several prospective and cross-sectional studies in different countries have reported the inverse association of social class with cardiovascular morbidity and mortality independent of conventional risk factors or access to health care, and this association was also found in countries with universal healthcare systems, as in our country [8][9][10][11].…”
Section: Discussionsupporting
confidence: 66%
“…Cooper et al [9] studied the relationship of endothelial dysfunction with SES measured by education, occupation, and income indicators in 72 healthy adults and found that patients with lower SES reported reduced endothelial function, suggesting that impaired arterial endothelial function, which often precedes CAD, could be a possible pathway linking SES with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…b In United States, this refers to current or past Duncan SEI score; in Japan, this refers to holding a professional/managerial occupation. community reference group however defined by the respondent, which makes it relevant to mental and physical health outcomes (see also Cooper et al, 2010;Ghaed and Gallo, 2007;Wolff et al, 2010).…”
Section: Subjective Social Status (Sss-community)mentioning
confidence: 99%
“…In young medical students, showing a high incidence of stress, smoking, unhealthy nutritional habits, and sedentary lifestyle, the main factors which determine endothelial function imbalance were stress and smoking [67]. Both objective and subjective socioeconomic status were related to brachial artery flow-mediated dilatation in healthy adults; the MacArthur Scale of Subjective Social Status, which assessed perceived social standing in the local community, positively correlated with flowmediated dilatation; no other socioeconomic status measures were significant for flow-mediated dilatation [17]. Lower subjective social status in one's community may be linked to cardiovascular disease via impaired vasodilatation.…”
Section: Effects Of Chronic Stressmentioning
confidence: 99%